Model identification and elimination of displays of actors threatening emergencies at the airport - Лобанчикова, Н.М. (Proceedings of National Aviation University (archive), 2009)
In the article is offered model of exposure and liquidation of displays of subjects of threats of origin of extraordinary situations on territory of air-port is offered.